Tri-band Minkowski Island split ring resonator patch antenna for WLAN and 5G applications - Hassan, Nornikman; Ahmad, Badrul Hisham; Ab Rashid, Amier Hafizun; Azemi, Saidatul Norlyana (2024)
This research investigates the effects of the Minkowski Island split ring resonator (MI-SRR) on the patch antenna. Initially, a Minkowski Island patch antenna design, Antenna A, was created in the CST Microwave Studio. Incorporating different diameters of the MI-SRR on the substrate resulted in three distinct resonant frequencies, shown as in Antenna B and Antenna C. This tri-band antenna performs best at 2.40 GHz, 3.52 GHz, and 5.22 GHz of resonant frequencies, with return losses of -21.945 dB, -17.154 dB, and -16.536 dB, respectively.